Application of reflexotherapy using the "balancing hexagrams" method in complex rehabilitation of compression-ischemic neuropathy of the femoral-genital nerve - Svyrydova, Nataliа; Gusev, Taras; Martseniuk, Igor; Sibiryakin, Yaroslav; Chupryna, Gennadii; Sereda, Vitaly (My University, 2024)
This article is devoted to one of the important problems of neurology – compression-ischemic neuropathy of the peripheral nerve. With such disorders, we often deal with pain. Various diseases, especially those that occur with a pain syndrome, manifest themselves in a protracted course. It often happens when there is some viscerogenic problem that complicates the situation: and the task of the reflexologist to whom the patient turned is to identify this problem – namely, to identify the problematic meridian of acupuncture and using its connections (and the method of «balancing hexagrams» – this is the establishment of inter-meridian connections) to act on them. The article provides an analysis of data from a sociological study conducted in May 2024 among students of the Interregional Academy of Personnel Management (Kyiv) aimed at identifying pathways to self-realization among students. Ця стаття присвячена одній з важливих проблем неврології – компресійно-ішемічній невропатії периферичного нерва. При таких розладах ми часто маємо діло з болем. Різні захворювання, особливо ті, що протікають з больовим синдромом, проявляються затяжним перебігом. Часто це буває, коли є якась вісцерогенна проблема, що ускладнює ситуацію: і задача лікаря-рефлексотерапевта, до якого звернувся пацієнт, виявити цю проблему – а саме, виявити проблемний меридіан акупунктури і використовуючи його зв’язки (а метод «балансування гексаграм» – це і є встановлення міжмеридіанних зв’язків) подіяти на них.
Keywords: реабілітація; rehabilitation; рефлексотерапія; reflexotherapy